Improving artistic jump at beam - Oltean, A.; Dobrescu, T.; Popescu, R. (Science, Movement & Health, 2018)
Objectives. The aim of the research is to develop the explosive force at the lower limbs in artistic jump at the beam in artistic gymnastics. The application of plyometric exercises with and without difficulties will lead to the development of the explosive force at the lower limbs and implicitly of the technique of execution of the artistic elements specific to the apparatus beam. Methods of research. The study was conducted on 2 groups of 10 gymnasts each during a year. The drive systems were designed with and without difficulties, elastic bands, sponge cubes and gym bench. To achieve the plyometric exercise program, we used an elastic support attached to the sports belt of gymnast. During the research two tests were carried out involving 3 motor tests and 4 technical tests. The motor tests focused on lower limb force and the technical tests concerned specific elements of the competition exercises. Results. Considering the application of the plyometric means of the proposed and performed exercises in the experimental group, it is noteworthy that this group obtained statistically significant meanings compared to the control group in the same tests. These results demonstrate a significant increase in the sports performance of the experiment group. At the same time, the applied tests show a positive value added for the gymnasts practicing this branch as evidenced by the results of the official competitions of these athletes in this category. Conclusions. We believe that the program developed and applied has had the expected effects and therefore we propose further training that includes the plyometric exercises for developing the explosive force of the gymnasts.